Developing a resilience intervention approach for adolescents living with natural hazards risks: A pilot randomized controlled trial. (May 2021) - Niu, Ying; Jiang, Xiaolian; Ashong, Zhuomawumao; Hou, Jinfeng; Bai, Yubing; Bai, Gazang; Xu, Junjun; Ren, Wenyu; Geng, Gazhaxi
Abstract: Increasing natural disasters have caused immediate and chronic psychosocial problems on adolescent survivors. Resilience-related skills are crucial for adolescents' recovery from and prevention against negative consequences, but relevant interventions are limited, especially for Tibetan adolescents. This study aimed to develop, implement, and preliminarily evaluate a culturally-attuned resilience intervention for Tibetan adolescent survivors living with natural hazards risks in China. The intervention was developed based on the 7Cs model of resilience (competence, confidence, connection, character, contribution, coping, and control), and Tibetan adolescents' resilience characteristics by interviewing adolescents, their teachers and experts. A pilot randomized controlled trial was conducted at three Yushu senior middle schools among Tibetan adolescent survivors at nine years after the 2010 Yushu earthquake in 2019. The intervention group attended nine 90-min sessions on learning competence, self-confidence, coping, interpersonal competence, and earthquake preparedness, and provided feedback after intervention. Both groups completed questionnaires about resilience, mental health, learning competence, self-esteem, coping, and interpersonal competence before and after the project. Compared with the control group ( n  = 28), the intervention group ( n  = 28) showed significant improvement in mental health, learning competence, coping, and interpersonal competence, but no significant difference in resilience and self-esteem was found. Most adolescents had a good impression (58.3%–100%) and high or moderate participation (91.7%–100%) of each intervention session. The intervention is feasible and acceptable, and shows preliminary effect in improving Tibetan adolescents' psychosocial well-being. Future research can tailor this resilience intervention to other developmental stages of adolescent survivors in other contexts with a large sample to benefit wider populations. Highlights: The development of a resilience intervention for adolescents living with natural hazard risks was described. It was the first to incorporate the 7Cs of resilience into intervention design for this population. It integrated daily-life resilience and disaster resilience, MHPSS and DRR. It demonstrated preliminary effect on resilience and psychosical well-being.